Developing public-private partnerships for effective access and use of climate information services by farmers and pastoralists in the great green wall intervention zone of Mali - Traoré, Bouba; Bouaré, Yaya; Nikoi, Gordon; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Through this initiative of public private partnership development, ICRISAT/CCAFS aims to analyze the partnership’s environment to establish the public private partnership required to promote the sustainable use of climate services and agro-advisories for improving management of climatic risks by farmers and pastoralists from the GGW area in Mali. The purpose of this initiative is to analyze the already existing partnership in the climate information framework in order to propose a "win-win" "public private" partnership models for the current and future climate information services providers to the farmers and agro-pastoralists in the GGW area in Mali.